The role of children's bone marrow mesenchymal stromal cells in the ex vivo expansion of autologous and allogeneic hematopoietic stem cells. (20th May 2015) - Pelagiadis, Iordanis; Stiakaki, Eftichia; Choulaki, Christianna; Kalmanti, Maria; Dimitriou, Helen
Abstract: The recognition of the role of Mesenchymal Stromal Cells (MSC) in hematopoiesis, as part of the bone marrow microenvironment, renewed the interest for cord blood (CB) ex vivo expansion as a source of HSC for transplantation. MSC from children are recognized to have different biological properties compared to the ones from adults. The current study focuses on the evaluation of the effects of children's bone marrow MSC on the ex vivo expansion capacity of both allogeneic cord blood and autologous bone marrow (BM) CD34 + hematopoietic stem cells (HSCs) when used as a cell feeder layer with or without recombinant cytokines. Our results showed that children's bone marrow‐derived MSC expand more primitive populations in co culture with CD34 and that the expansion is further enhanced when the culture is supplemented with growth factors. No additive effect was seen either with the early‐ or late‐acting growth factors' cocktails used. Biological features of CB hematopoietic progenitors seem to make them more suitable than their BM counterparts for ex vivo expansion. Clinical implementation will be facilitated by methodological standardization and guidelines' establishment.